Recent advances in operator theory and applications - Ando, Tsuyoshi. (Operator theory: advances and applications,, 2009)
A Connection between Szegö and Nehari Sequences in the Matrix-valued Case -- Multivariable Generalizations of the Schur Class: Positive Kernel Characterization and Transfer Function Realization -- Some Problems Concerning the Test Functions in the Szegö and Avram-Parter Theorems -- On the Numerical Solution of a Hypersingular Integral Equation with Fixed Singularities -- Spectrum and Principal Function of Operators -- Spectral Consequences due to General Hölder’s Inequalities and Domination of Semigroups -- Quadratically Hyponormal Recursively Generated Weighted Shifts -- Relaxed Commutant Lifting: An Equivalent Version and a New Application -- Variants of Ando-Hiai Inequality -- On Local Spectral Theory -- The Finite Sections Approach to the Index Formula for Band-dominated Operators -- A New Proof that Rudin’s Module is not Finitely Generated -- Quasinilpotent Part of class A or (p, k)-quasihyponormal Operators -- A New Majorization Induced by Matrix Order -- H ? Functional Calculus and Characterization of Domains of Fractional Powers -- Operators on Locally Convex Spaces.